Probathylepadidae, a new family of Scalpelliformes (Thoracica: Cirripedia: Crustacea), for Probathylepas faxian gen. nov., sp. nov., from a hydrothermal vent in the Okinawa Trough - Ren, Xian-Qiu; Sha, Zhong-Li (Zootaxa, 2015)
A new pedunculate barnacle, Probathylepas faxian gen. and sp. nov., is described from a hydrothermal vent in the Okinawa Trough. A new scalpelliform family, Probathylepadidae, is also proposed for the new genus and species. Probathylepadidae differs from all other five families of the order Scalpelliformes by the capitulum bearing eight primal plates and two whorls of imbricating supplementary plates, and the peduncle being without scales. The relationships between the species of the new family and sessile barnacles are also discussed.